Endogenity of Performance Based On Work Environment, Creativity and Motivation - Riwu Kore, Jefirstson R; Manafe, Yoshilda Marisa; Wadud, Muhammad; Yustini, Tien (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: Analyse and prove the effect of work environment, creativity, and motivation on performance. Methodology: The research was conducted for 4 months, namely October 2024 - January 2025. The type of research is quantitative research. The research population was ASN in the Department of Industry and Trade of Kupang City as many as 93 employees. The entire population became the research sample with saturated sampling technique. The technique of obtaining data was carried out with a Likert scale questionnaire, observation, interviews, and documentation. The types of data obtained are primary and secondary data. Data analysis in this study is multiple linear regression, with the stages of instrument testing, classical assumption testing and hypothesis testing. Results: The results showed that work environment, creativity, and motivation have a positive and significant effect on performance, both partially and simultaneously. The contribution of work environment variables, creativity, and motivation to performance is 94.5%. Findings: The results of this study indicate that the implementation of work environment, creativity, and motivation has been in accordance with the needs of the organization, thus having an impact on employee performance. These three variables need to be maintained and increased exogeneity so that they have an endogeneity effect on employee performance. Novelty: This research contributes to developing comprehensive human resource management science and further research in this field. Â Originality: Improving employee performance in government organizations can be done by simultaneously paying attention to aspects of work environment, creativity, and motivation. Conclusion: The implementation of work environment, creativity, and motivation in the scope of Disperindag Kota Kupang needs to be maintained and improved because it has a positive and significant influence on employee performance. Type of Paper: Empirical research paper.